Effect of nitrogen reduction combined with biochar application on soda saline soil and soybean growth in black soil areas - Xu, Bo; Li, Hongyu; Wang, Qiuju; Li, Quanfeng; Sha, Yan; Ma, Chen; Yang, Aizheng; Li, Mo (Frontiers in Plant Science, 2024)
The combination of biochar and nitrogen (N) fertilization in agricultural salt-affected soils is an effective strategy for amending the soil and promoting production. To investigate the effect of nitrogen reduction combined with biochar application on a soda saline soil and soybean growth in black soil areas, a pot experiment was set up with two biochar application levels, 0 (B0) and 4.5 t/hm2 (B1); two biochar application depths, 0-20 cm (H1) and 0-40 cm (H2); and two nitrogen application levels, conventional nitrogen application (N0) and nitrogen reduction of 15% (N1). The results showed that the application of biochar improved the saline soil status and significantly increased soybean yield under lower nitrogen application. Moreover, increasing the depth of biochar application enhanced the effectiveness of biochar in reducing saline soil barriers to crop growth, which promoted soybean growth. Increasing the depth of biochar application increased the K+ and Ca2+ contents, soil nitrogen content, N fertilizer agronomic efficiency, leaf total nitrogen, N use efficiency, AN, Tr, gs, SPAD, leaf water potential, water content and soybean yield and its components. However, the Na+ content, SAR, ESP, Na+/K+, Ci and water use efficiency decreased with increasing biochar depth. Among the treatments with low nitrogen input and biochar, B1H1N1 resulted in the greatest soil improvement in the 0-20 cm soil layer compared with B0N0; for example, K+ content increased by 61.87%, Na+ content decreased by 44.80%, SAR decreased by 46.68%, and nitrate nitrogen increased by 26.61%. However, in the 20-40 cm soil layer, B1H2N1 had the greatest effect on improving the soil physicochemical properties, K+ content increased by 62.54%, Na+ content decreased by 29.76%, SAR decreased by 32.85%, and nitrate nitrogen content increased by 30.77%. In addition, compared with B0N0, total leaf nitrogen increased in B1H2N1 by 25.07%, N use efficiency increased by 6.7%, N fertilizer agronomic efficiency increased by 32.79%, partial factor productivity of nitrogen increased by 28.37%, gs increased by 22.10%, leaf water potential increased by 27.33% and water content increased by 6.44%. In conclusion, B1H2N1 had the greatest effect on improving the condition of saline soil; it not only effectively regulated the distribution of salt in soda saline soil and provided a low-salt environment for crop growth but also activated deep soil resources. Therefore, among all treatments investigated in this study, B1H2N1 was considered most suitable for improving the condition of soda saline soil in black soil areas and enhancing the growth of soybean plants.